Pengaruh Pendidikan Kesehatan terhadap Tingkat Pengetahuan tentang Imunisasi Polio dan Pentabio pada Ibu yang Memiliki Anak (Usia 0-6 Bulan) di Wilayah UPTD Puskesmas Kayon Palangka Raya: The Effect of Health Education on the Level of Knowledge of Polio and Pentabio Immunization in Mothers who Have Children (Ages 0-6 Months) UPTD Puskesmas Kayon Palangka Raya - Indriani Indriani; Vita Natalia; Wika Sari (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Background Polio immunization is used to prevent poliomyelitis disease that can cause paralysis in infants. The disease is caused by a poliomyelitis virus that enters through the food, breeds in the gastrointestinal lymph nodes, then spreads through the blood to the nervous system, resulting in paralysis or lifelong disability. Immunization of combined pentabio DPT-HB and Hib vaccine. Pentabio immunization prevents certain diseases, such as diphtheria, whooping cough, tetanus, hepatitis B, meningitis, and pneumonia caused by Hib bacteria (Haemophilus influenza type b). The phenomenon that occurred at Kayon Health Center when interviewed, there are still many mothers who are less aware of polio and pentabio immunization. Objectives The purpose of this study was to determine the effect of health education on the level of knowledge about polio immunization in mothers who have babies (aged 0-6 months) in the UPTD Work Area of the Kayon Health Center Palangka Raya. The design used in this study uses a pre-experimental research design with a